Active Power Filter LCL Filter Insertion Loss Calculation Analysis - Asmanis, G.; Krievs, O.; Asmanis, A. (Elektronika ir Elektrotechnika, 2012)
This paper introduces a new approach for active power filters LCL filter insertion loss calculation, treating it as two port T-network and describing it using scattering and impedance parameters. There is proposed usage of line impedance stabilization network in frequency range over 9kHz to enable insertion loss calculation neglecting mains impedance. In the study, importance of parasitic elements of LCL filter components is analyzed. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2799